The Role of Matrix Metalloproteinase-9 in Atherosclerotic Plaque Instability - Tiewei Li; Xiaojuan Li; Yichuan Feng; Geng Dong; Yuewu Wang; Junmei Yang (Hindawi Limited, 2020)
Matrix metalloproteinase-9 (MMP-9) belongs to the MMP family and has been widely investigated. Excessive MMP-9 expression can enhance extracellular matrix degradation and promote plaque instability. Studies have demonstrated that MMP-9 levels are higher in vulnerable plaques than in stable plaques. Additionally, several human studies have demonstrated that MMP-9 may be a predictor of atherosclerotic plaque instability and a risk factor for future adverse cardiovascular and cerebrovascular events. MMP-9 deficiency or blocking MMP-9 expression can inhibit plaque inflammation and prevent atherosclerotic plaque instability. All of these results suggest that MMP-9 may be a useful predictive biomarker for vulnerable atherosclerotic plaques, as well as a therapeutic target for preventing atherosclerotic plaque instability. In this review, we describe the structure, function, and regulation of MMP-9. We also discuss the role of MMP-9 in predicting and preventing atherosclerotic plaque instability.